Weight watchers our best quick & easy meals. - Kirkland, Andrea C. (Des Moines, IA : Oxmoor House, Inc., 2010)
Step-by-step instructions and nutritional analyses for 116 menus with POINTS® values of 8 or less.
INTRODUCTION -- Cook fast eat well -- About the recipes -- RECIPES -- Breakfast -- Fish & shellfish -- Meatless main dishes -- Meats -- Poultry -- Salads -- Sandwiches -- Soups -- Desserts.
Includes index.
Keywords: LOW-CALORIE DIET -- RECIPES